Unicystic ameloblastoma of the maxillary sinus: Pitfalls of diagnosis and management - Pitak-Arnnop, P (LITHOGRAPHIA Antoniadis I.-Psarras Th. G.P., 2010)
Background: Ameloblastoma is a common odontogenic tumor of the jaws that comprises 3 variants: conventional (solid), unicystic and peripheral ameloblastomas. Unicystic ameloblastoma (UA) in the maxillary sinus is very rare. With a secondary infection, the clinical features may lead to incorrect diagnosis and treatment. Patients and Methods: A 19-year-old man was referred for the management of sinusitis and a mass at the right cheek. A few weeks earlier, the patient presented with acute cellulitis at the same area and underwent an incision and drainage in a primary care unit without any appropriate investigation. A radiographic examination revealed a massive lesion in the right maxillary sinus. An unerupted tooth within the lesion was found at the level of the orbital floor. Results: The patient was successfully treated by enucleation of the tumor and curettage. The specimen was sent for histopathological examination, and the definite diagnosis was UA. The patient has been followed-up periodically for 5 years without recurrence. Discussion: This case report suggests that primary care doctors should pay attention to differential diagnosis of orofacial lesions. It is therefore of great benefit to organize continuing education for general physicians who initially meet oral disease patients as a 'gate keeper'. Errors of clinical diagnosis and management of orofacial lesions would be minimized. Pitfalls of diagnosis and management of UA in the maxillary sinus were briefly reviewed.